Dynamics of the three methionyl side chains of Streptomyces subtilisin inhibitor. Deuterium NMR studies in solution and in the solid state. - Tamura, A. (Cold Spring Harbor Laboratory Press, 1996)
Streptomyces subtilisin inhibitor (SSI) contains three methionine residues in a subunit: two (at positions 73 and 70) in the crucial enzyme-recognition sites P1 and P4, respectively, and one (Met 103) in the hydrophobic core. The motions of the side chains of these three Met residues and the changes in mobility on binding with subtilisin were studied by deuterium NMR spectroscopy in solution and in crystalline and powder solids. For this purpose, the wild-type SSI was deuterium-labeled at the methyl groups of all three Met residues, and three artificial mutant proteins were labeled at only one specific Met methyl group each. In solution, for methionines 73 and 70, the effective correlation times were only 0.8-1.0 x 10(-10)s indicating that the two side chains on the surface fluctuate almost freely. On formation of a complex with subtilisin, however, these high mobilities were quenched, giving a correlation time of 1.1 x 10(-8)s for the side chains of methionines 70 and 73. The correlation time of Met 103, located in the hydrophobic core, was at least 1.0 x 10(-8)s in free SSI, showing that its side chain motion is highly restricted. The nature of the internal motions of the three Met side chains was examined in more detail by deuterium NMR spectroscopy of powder and crystalline samples. The spectral patterns of the powder samples depended critically on hydration: immediately after lyophilization, the side-chain motions of the three Met residues were nearly quenched. With gradual hydration to 0.20 gram of water per gram protein-water, the orientational fluctuation of the methyl axes of methionines 70 and 73 was selectively enhanced in both amplitude and frequency (to about 1 MHz) and, at nearly saturating hydration (0.60 gram of water per gram protein-water), became extremely high in amplitude and frequency (> 10 MHz). In contrast, the polycrystalline wild-type SSI spectrum showed fine structures, reflecting characteristic motions of the Met side chains. The polycrystalline spectrum could be reproduced reasonably well by the same motion models and parameters used to simulate the powder spectrum at the final level of hydration, suggesting that the side-chain motions are similar in the fully hydrated powder and in crystals. Spin-lattice relaxation measurements gave evidence that, even in crystals, the methyl axes of all three Met residues undergo rapid motions with correlation times between 10(-8) and 10(-10)s, comparable to the correlation times in solution. Finally, in the hydrated stoichiometric complex of SSI with subtilisin BPN' in the solid state, large-amplitude motions are absent, but the side chains of methionines 70 and/or 73 are likely to have small-amplitude motions.